The Role of Al-Mu’iz Lidinillah in Shaping the Cultural Identity of the Fatimid Dynasty in Egypt and Its Implications for Islamic Cultural Education - Elvina Ardiani Bugis; Salsabila Azizah; Violeta Inayah Pama (Global Action and Education for Society, 2026)
Al-Mu’iz Lidinillah is one of the most influential caliphs of the Fatimid Dynasty in history. He ruled Egypt for more than 20 years and left a significant legacy in the fields of architecture, education, and culture. This journal will discuss the role of Al-Mu’iz Lidinillah in shaping the cultural identity of the Fatimid Dynasty in Egypt. The research method used is library research, which obtains data thru readings related to the discussed research, such as books, magazines, journals, and others. The research results show that Al-Mu’iz Lidinillah's role in shaping the cultural identity of the Fatimid Dynasty can be seen in the development of architecture, education, and the arts and culture. Al-Mu’iz Lidinillah is one of the most influential caliphs of the Fatimid Dynasty in history. He ruled Egypt for more than 20 years and left a significant legacy in the fields of architecture, education, and culture. This journal will discuss the Role of Al-Mu’iz Lidinillah in Shaping the Cultural Identity of the Fatimid Dynasty in Egypt. The research method used is library research, which obtains data thru readings related to the discussed research, such as books, magazines, journals, and others. The research results show that Al-Mu’iz Lidinillah's role in shaping the cultural identity of the Fatimid Dynasty can be seen in architectural development, educational advancement, and the development of arts and culture.